x+2分之x=1=( )分之2x+2=3x+6分之( )=( )分之x^2+x=2x^3+4x^2分之( )
2个回答
本团长来帮你
(x+2)分之(x+1)=(2x+4 )分之(2x+2)=(3x+6)分之( 3x+3)=(x²+2x )分之(x²+x)=(2x³+4x²)分之(2x³+2x² )
相关问题
(1) x-2分之4x-1=2-x分之3 (2) x-3分之x-2x-6分之1=2分之1 (3) x+3分之x=1+x-
x-2分之4x-(1)=2-x分之3 x-3分之x-2x-6分之1=2分之1 x+3分之x=1+x-1分之2 解分式方程
3分之x+1-2分之4-x=6分之x-2 5分之y-2分之y-1=2-5分之y+2 x-2分之x-1=3分之2-3分之x
(1)2分之5-3x=3分之3+5x (2)4分之x+2-6分之2x-3=1 (3)12分之x-1=15分之2x (4)
(1)x+3分之3=4 (2)x-1分之2=x+1分之3 (3)2x-1分之5+1-2x分之3=2 (4)x分之1+2x
解方程 1-3分之4-5X=4分之2X+1-2(2-X) 5分之2X-3-6分之3X-1=3分之1X 3分之2X-1-2
解方程 1-3分之4-5X=4分之2X+1-2(2-X) 5分之2X-3-6分之3X-1=3分之1X 3分之2X-1-2
2分之5x+3=3分之1+7x 3分之x-5=2分之5-x 3分之x-2=1-4分之x 1-4分之4-3x=6分之5X+
解方程:3分之X+3-1=4分之2+X 2分之X-4=X-6分之1-2X
6分之3-X-5分之X-4=3分之2X+2-2的解和4分之X-3分之6-X=1-2分之X的值,